Madrid yearly review 2018 International registration of marks - World Intellectual Property Organization (Geneva, Swittzerland WIPO, 2018)
Comprehensive facts, figures and analysis of the international registration of marks. Datos completos, cifras y análisis del registro internacional de marcas.
Keywords: PROPIEDAD INTELECTUAL -- MARCAS